Self-talk vs crosstalk: extracellular particles derived from myoblasts and fibroblasts and their effects on myoblast function and related myogenic regulatory factors - Hagemann, Kyle Nicholas (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.